Eloise's rawther unusual Halloween [videorecording (DVD)] - Goldmann, Steven; Archer, Wesley, 1961-; Mouser, Mary Matilyn, 1996-; Curry, Tim; Belushi, James, 1954-; Garrett, Brad, 1960-; Redgrave, Lynn, 1943-2010; Thompson, Kay, 1909-1998 (Eloise., 2008)
Every Halloween, the ghost of the Plaza's most legendary and outrageous inhabitant of old, Diamond Jim Johnson, returns to haunt the halls. There are tricks and treats galore in store when Eloise busts some ghosts and reverses a curse.